(untitled) (Journal of Dhaka Medical College, 2010)
Objectives: This study was conducted to find out the problems faced by the kith and kin (children) to deal with their aged parents. Methodology: This cross-sectional descriptive study was conducted among the rural people of Dhamrai, who had either one or both living parents. Data was collected from January to March, 2008. Results: Three hundred respondents were interviewed; the mean age was 33.73 (S.D ±7.27) years. Most of the respondents were Muslims (92%) and male (86%). Majority were day labourer (37.3%), agriculture worker (26%) and businessman (19.3%). Rests were service holders (11.3%) and housewives (9%). The educational levels of the respondents were SSC and above (41%) while 8.6% were illiterate. Mean family size was 5.5 members with mean average monthly income 4173(S.D ±2007.77) taka. Majority of the respondents (58.3%) had their parents living with them and 92% parents were dependant upon them for their living. More than half (56%) respondents had problems due to the presence of their parents in their families. Among them, majority (63%) had financial constrain, others were too busy with occupation (18%), limited space in their houses (10%), due to pressure from family members family members (9%). More financial support (32%), more attention (31%), more honour (20%) were the main expectations from their kith and kin by the parents. Conclusion: The main problems found among the majority (56%) of the respondents were, financial constraint (63%), busy with occupation (18%), limited space at home(10%), and non co-operation from other family members(9%). Key Words: Kith & Kin; Caregivers; Elderly DOI: 10.3329/jdmc.v17i2.6592 J Dhaka Med Coll. 2008; 17(2) : 106-110